Accelerating Photostability Evaluation of Perovskite Films through Intelligent Spectral Learning-Based Early Diagnosis - Liu, Ziyi; Zhang, Jiyun; Rao, Gaofeng; Peng, Zijian; Huang, Yixing; Arnold, Simon; Liu, Bowen; Deng, Can; Li, Chen; Li, Heng; Zhi, Hanxiang; Zhang, Zhi; et al. (ACS Energy Letters, 2024)
Obtaining highly stable metal-halide perovskites is crucial for the commercialization of perovskite solar cells. However, current methods for evaluating perovskite stability mainly rely on a time-consuming and resource-intensive aging process. Here, we demonstrate a spectral learning-based methodology that enables the prediction of perovskite stability by leveraging the features in photoluminescence and absorption spectra of fresh perovskite films. This methodology circumvents the long-term aging process by combining a custom-developed spectral feature extraction algorithm and an integrated voting machine learning model. By integration of the early diagnosis program with high-throughput experiments, the prediction accuracy for stable perovskites exceeds 86% in 160 fresh samples. The universality is further examined by another batch of 224 fresh samples fabricated through different processing conditions. Finally, the early diagnosis of perovskite films is successfully translated to enhanced stability in perovskite solar cells. Our work provides a new pathway to accelerate the discovery and development of stable perovskite films.
Created from Fastlane, Scopus look-up

A High Throughput Platform to Minimize Voltage and Fill Factor Losses - Haffner-Schirmer, Julian; Le Corre, Vincent Marc; Forberich, Karen; Egelhaaf, Hans-Joachim; Osterrieder, Tobias; Wortmann, Jonas; Liu, Chao; Weitz, Paul; Heumüller, Thomas; Bornschlegl, Andreas; Wachsmuth, Josua; Distler, Andreas; et al. (Advanced Energy Materials, 2025)
Organic photovoltaics (OPV) now can exceed 20% power conversion efficiency in single junction solar cells. To close the remaining gap to competing technologies, both fill factor and open-circuit voltage must be optimized. The Langevin reduction factor is a well-known concept that measures the degree to which charge extraction is favored over charge recombination. It is therefore ideally suited as an optimization target in high-throughput workflows; however, its evaluation so far requires expert interaction. Here, an integrated high-throughput workflow is presented, able to obtain the Langevin reduction factor within a few seconds with high accuracy without human intervention and thus suited for autonomous experiments. This is achieved by combining evidence from UV–vis spectra, current–voltage curves, and a novel implementation of microsecond transient absorption kinetics allowing, for the first time, the intrinsic determination of charge absorption cross-sections, which is crucial to reporting stationary charge densities. The method is demonstrated by varying the donor:acceptor ratio of the high performance OPV blend PM6:Y12. The high reproducibility of the method allows to find a strictly exponential relationship between the PM6 exciton energy and the Langevin reduction factor.
CRIS-Team Scopus Importer:2025-01-31
Keywords: charge dynamics; high throughput; Langevin reduction factor; organic photovoltaics; transient absorption kinetics

Binary cations minimize energy loss in the wide-band-gap perovskite toward efficient all-perovskite tandem solar cells - Zhang, Kaicheng; Liu, Chao; Peng, Zijian; Li, Chaohui; Tian, Jingjing; Li, Canru; García Cerrillo, José; Dong, Lirong; Streller, Fabian; Späth, Andreas; Musiienko, Artem; Englhard, Jonas; et al. (Joule, 2024)
Perovskite-based tandem solar cells stand at the forefront of photovoltaic innovation due to their exceptional performance and cost-effective fabrication. This study focuses on minimizing energy losses within a 1.80 eV perovskite sub-cell. We demonstrate that the surface treatment of perovskite with binary guanidinium bromide and 4-fluorophenylammonium iodide synergistically reduces defect densities and adjusts interfacial energy-level alignment. The enhanced passivation effect and the formation of a surface dipole significantly reduce nonradiative recombination and transport losses, leading to a notable increase in the open-circuit voltage and fill factor product, thereby achieving an impressive power conversion efficiency (PCE) of 19.0%. The reproducibility of these findings is confirmed by consistent results across different laboratories. Furthermore, integration with a narrow-band-gap perovskite yields an all-perovskite tandem device with a PCE of 27.2%. This comprehensive understanding of the pivotal role of spacer cations in surface treatment significantly advances the pathway toward efficient perovskite photovoltaics.
CRIS-Team Scopus Importer:2024-08-30
Keywords: 2D phases; all-perovskite tandem solar cell; energy loss; energy-level alignment; nonradiative recombination; passivation; spacer cations; surface dipole; surface treatment; wide band-gap perovskite

Controlling Intermediate Phase Formation to Enhance Photovoltaic Performance of Inverted FA-Based Perovskite Solar Cells - Li, Chaohui; Park, Hyoungwon; Qiu, Shudi; Streller, Fabian; Zhang, Kaicheng; Peng, Zijian; Byun, Jiwon; Tian, Jingjing; Maiti, Santanu; Xie, Zhiqiang; Dong, Lirong; Liu, Chao; et al. (ACS Energy Letters, 2024)
Formamidinium (FA)-based perovskites exhibit significant potential for highly efficient photovoltaics due to their promising optoelectronic properties and optimal bandgap. However, the undesired inactive phase arises from multiple crystal nucleation pathways formed by various intermediate phases during the film formation process, persistently accompanying it. FA-based perovskites frequently struggle to form uniform, highly crystalline films. This challenge complicates the development of reliable and highly reproducible crystallization processes for perovskites and the establishment of guidelines for controlling the α-phase formation. In this work, we investigate the role of poly(acrylonitril-co-methyl acrylate) (PAM) to simultaneously control nucleation and subsequent α-phase crystallization. This successfully demonstrates the regulation of oriented crystal growth through the creation of a PAM-PbI2 intermediate. Ultimately, PAM-modified p-i-n architecture devices obtain a promising power conversion efficiency (PCE) of 25.30%, with VOC (1.211 V), achieving 95% of the detailed balance limit. Additionally, PAM-modified devices maintain ≥90% of the initial efficiency for 1000 h under 1 sun and 65 °C operation.
CRIS-Team Scopus Importer:2024-11-22

Durable all-inorganic perovskite tandem photovoltaics - Duan, Chenghao; Zhang, Kaicheng; Peng, Zijian; Li, Shiang; Zou, Feilin; Wang, Feng; Li, Jiong; Zhang, Zheng; Chen, Chang; Zhu, Qiliang; Qiu, Jianhang; Lu, Xinhui; et al. (Nature, 2025)
All-inorganic perovskites prepared by substituting the organic cations (for example, methylammonium and formamidinium) with inorganic cations (for example, Cs+) are effective concepts to enhance the long-term photostability and thermal stability of perovskite solar cells (PSCs)1,2. Hence, inorganic perovskite tandem solar cells (IPTSCs) are promising candidates for breaking the efficiency bottleneck and addressing the stability issue, too3,4. However, challenges remain in fabricating two-terminal (2T) IPTSCs due to the inferior film formation and deep trap states induced by tin cations5-7. Here a ligand evolution (LE) strategy with p-toluenesulfonyl hydrazide (PTSH) is used to regulate film formation and eliminate deep traps in inorganic narrow-bandgap (NBG) perovskites, enabling the successful development of 2T IPTSCs. Accordingly, the 1.31 eV CsPb0.4Sn0.6I3:LE device delivers a record efficiency of 17.41%. Combined with the 1.92 eV CsPbI2Br top cell, 2T IPTSCs exhibit a champion efficiency of 22.57% (certified, 21.92%). Moreover, IPTSCs are engineered to deliver remarkable durability under maximum power point (MPP) tracking, maintaining 80% of their initial efficiency at 65 °C for 1,510 h and at 85 °C for 800 h. We elucidate that LE deliberately leverages multiple roles for inorganic NBG perovskite growth and anticipate that our study provides an insightful guideline for developing high-efficiency and stable IPTSCs.
CRIS-Team Scopus Importer:2025-02-17

Efficient, stable, and fully printed carbon-electrode perovskite solar cells enabled by hole-transporting bilayers - Du, Tian; Qiu, Shudi; Zhou, Xin; Le Corre, Vincent Marc; Wu, Mingjian; Dong, Lirong; Peng, Zijian; Zhao, Yicheng; Jang, Dongju; Spiecker, Erdmann; Brabec, Christoph; Egelhaaf, Hans-Joachim (Joule, 2023)
Printable planar carbon electrodes emerge as a promising replacement for thermally evaporated metals as the rear contact for perovskite solar cells (PSCs). However, the power conversion efficiencies (PCEs) of the state-of-the-art carbon-electrode PSC (c-PSC) noticeably lag behind their metal-electrode counterparts. Here, we propose a hole-transporting bilayer (HTbL) configuration to improve the fill factor and the open-circuit voltage of c-PSCs simultaneously. The HTbL is prepared by sequentially blade coating two organic semiconductors between perovskite and carbon, with the outer HTL enhancing hole extraction to carbon, while the inner HTL mitigates perovskite surface recombination. Consequently, our fully printed c-PSCs with HTbL outperform those with single HTL, and a stabilized champion PCE of 19.2% is achieved compared with that of 17.3%. Our prototype c-PSC stably operates during 1 sun, 65°C aging test (ISOS-L-2I) for 2,500 h showing negligible PCE drop, validating its potential as a highly cost-effective photovoltaic technology.
CRIS-Team Scopus Importer:2023-08-18
Keywords: bilayer; carbon electrode; fully printed perovskite solar cells; hole transporting; stability

Overcoming optical losses in thin metal-based recombination layers for efficient n-i-p perovskite-organic tandem solar cells - Tian, Jingjing; Liu, Chao; Forberich, Karen; Barabash, Anastasia; Xie, Zhiqiang; Qiu, Shudi; Byun, Jiwon; Peng, Zijian; Zhang, Kaicheng; Du, Tian; Sathasivam, Sanjayan; Macdonald, Thomas J.; et al. (Nature Communications, 2025)
Perovskite-organic tandem solar cells (P-O-TSCs) hold substantial potential to surpass the theoretical efficiency limits of single-junction solar cells. However, their performance is hampered by non-ideal interconnection layers (ICLs). Especially in n-i-p configurations, the incorporation of metal nanoparticles negatively introduces serious parasitic absorption, which alleviates photon utilization in organic rear cell and decisively constrains the maximum photocurrent matching with front cell. Here, we demonstrate an efficient strategy to mitigate optical losses in Au-embedded ICLs by tailoring the shape and size distribution of Au nanoparticles via manipulating the underlying surface property. Achieving fewer, smaller, and more uniformly spherical Au nanoparticles significantly minimizes localized surface plasmon resonance absorption, while maintaining efficient electron-hole recombination within ICLs. Consequently, optimized P-O-TSCs combining CsPbI2Br with various organic cells benefit from a substantial current gain of >1.5 mA/cm2 in organic rear cells, achieving a champion efficiency of 25.34%. Meanwhile, optimized ICLs contribute to improved long-term device stability.
CRIS-Team Scopus Importer:2025-01-31

Precise control of process parameters for >23% efficiency perovskite solar cells in ambient air using an automated device acceleration platform - Zhang, Jiyun; Wu, Jianchang; Barabash, Anastasia; Du, Tian; Qiu, Shudi; Le Corre, Vincent Marc; Zhao, Yicheng; Zhang, Kaicheng; Schmitt, Frederik; Peng, Zijian; Tian, Jingjing; Li, Chaohui; et al. (Energy and Environmental Science, 2024)
Achieving high-performance perovskite photovoltaics, especially in ambient air, is critically dependent on the precise optimization of process parameters. However, traditional manual methods often struggle to effectively control the key variables. This inherent challenge requires a paradigm shift toward automated platforms capable of precise and reproducible experiments. Herein, we use a fully automated device acceleration platform (DAP) to optimize air-processed parameters for preparing perovskite devices using a two-step sequential deposition technique. Over ten process parameters with significant potential to influence device performance are systematically optimized. Specifically, we delve into the impact of the dripping speed of organic ammonium halide, a parameter that is difficult to control manually, on both perovskite film and device performance. Through the targeted design of experiments, we reveal that the dripping speed significantly affects device performance primarily by adjusting the residual PbI2 content in the films. We find that optimal dripping speeds, such as 50 µL s−1, contribute to top-performance devices. Conversely, excessively fast or slow speeds result in devices with comparatively poorer performance and lower reproducibility. The optimized parameter set enables us to establish a standard operation procedure (SOP) for additive-free perovskite processing in ambient conditions, which yield devices with efficiencies surpassing 23%, satisfactory reproducibility, and state-of-the-art photo-thermal stability. This research underscores the importance of understanding the causality of process parameters in enhancing perovskite photovoltaic performance. Furthermore, our study highlights the pivotal role of automated platforms in discovering innovative workflows and accelerating the development of high-performing perovskite photovoltaic technologies.
CRIS-Team Scopus Importer:2024-07-19

Precursor-Engineered Volatile Inks Enable Reliable Blade-Coating of Cesium–Formamidinium Perovskites Toward Fully Printed Solar Modules - Du, Tian; Rehm, Viktor; Qiu, Shudi; Pal, Subhajit; Jang, Dongju; Peng, Zijian; Zhang, Jiyun; Yuan, Haozhen; Briscoe, Joe; Heiß, Wolfgang; Brabec, Christoph; Egelhaaf, Hans-Joachim (Advanced Science, 2024)
Reliable fabrication of large-area perovskite films with antisolvent-free printing techniques requires high-volatility solvents, such as 2-methoxyethanol (2ME), to formulate precursor inks. However, the fabrication of high-quality cesium–formamidinium (Cs–FA) perovskites has been hampered using volatile solvents due to their poor coordination with the perovskite precursors. Here, this issue is resolved by re-formulating a 2ME-based Cs0.05FA0.95PbI3 ink using pre-synthesized single crystals as the precursor instead of the conventional mixture of raw powders. The key to obtaining high-quality Cs–FA films lies in the removal of colloidal particles from the ink and hence the suppression of colloid-induced heterogeneous nucleation, which kinetically facilitates the growth of as-formed crystals toward larger grains and improved film crystallinity. Employing the precursor-engineered volatile ink in the vacuum-free, fully printing processing of solar cells (with carbon electrode), a power conversion efficiency (PCE) of 19.3%, a T80 (80% of initial PCE) of 1000 h in ISOS-L-2I (85 °C/1 Sun) aging test and a substantially reduced bill of materials are obtained. The reliable coating methodology ultimately enables the fabrication of carbon-electrode mini solar modules with a stabilized PCE of 16.2% (average 15.6%) representing the record value among the fully printed counterparts and a key milestone toward meeting the objectives for a scalable photovoltaic technology.
CRIS-Team Scopus Importer:2024-05-24
Keywords: cesium formamidinium perovskite; reliable blade coating; single crystals; solar module; volatile ink

Quantifying the Energy Losses in CsPbI2Br Perovskite Solar Cells with an Open-Circuit Voltage of up to 1.45 v - Tian, Jingjing; Zhang, Kaicheng; Xie, Zhiqiang; Peng, Zijian; Zhang, Jiyun; Osvet, Andres; Lüer, Larry; Kirchartz, Thomas; Rau, Uwe; Li, Ning; Brabec, Christoph (ACS Energy Letters, 2022)
CsPbI2Br perovskite solar cells (PSCs) have attracted much interest because of their thermodynamic stability, relatively stable cubic perovskite phase, and their potential as a top cell for tandem applications. However, the open-circuit voltage (VOC) reported to date is in most cases well below the detailed balance (DB) limit for single-junction PSCs. Here, we demonstrate that adding lead acetate to the CsPbI2Br precursor allows us to substantially reduce losses due to nonradiative recombination. Corresponding champion devices reach a power conversion efficiency (-) of 16.7% and a highest VOC value of 1.45 V, which represents 90% of the DB limit for single-junction PSCs at a bandgap of 1.89 eV. In order to disentangle the nonradiative recombination loss mechanisms, we quantify the origin of energy losses by calculating the radiative limit of the open-circuit voltage (VOCrad) and the quasi-Fermi level splitting (QFLS) of perovskite films with and without other functional layers. We further analyze the strategies to reduce the residual losses in order to push the efficiency beyond the 90% theoretical limit.
CRIS-Team Scopus Importer:2022-11-18

Reducing Open-Circuit Voltage Losses in All-Inorganic Perovskite Cells by Dedoping - Peng, Zijian; Tian, Jingjing; Zhang, Kaicheng; These, Albert; Xie, Zhiqiang; Zhao, Yicheng; Osvet, Andres; Guo, Fei; Lüer, Larry; Li, Ning; Brabec, Christoph (ACS Energy Letters, 2023)
CsPbI2Br is an attractive photovoltaic material due to its promising optoelectronic properties. However, the corresponding perovskite solar cells (PSCs) with p-i-n configuration suffer from low open-circuit voltage (VOC) and fill factor (FF), limiting their application in tandem solar cells. Here, we propose using the fullerene ICBA as the electron charge transporting layer (ETL), forming a better interfacial contact and enhancing the internal quasi-Fermi level splitting (QFLS). A further reduction of VOC losses of around 0.1 V was achieved by an ultrathin phenethylammonium chloride (PEACl) layer between the perovskite and the ETL. We precisely study the VOC improvement and find that passivation of surface recombination contributes only 20 mV, while more importantly, a major increase of 80 mV is achieved by dedoping the perovskite surface, which removes a non-negligible electron extraction barrier. Our results give helpful direction regarding how to further improve VOC in p-i-n perovskite cells.
CRIS-Team Scopus Importer:2023-04-21

Revealing Degradation Mechanisms in 3D/2D Perovskite Solar Cells under Photothermal Accelerated Ageing - Peng, Zijian; Vincze, Andrej; Streller, Fabian; Le Corre, Vincent Marc; Zhang, Kaicheng; Li, Chaohui; Tian, Jingjing; Liu, Chao; Luo, Junsheng; Zhao, Yicheng; Späth, Andreas; Fink, Rainer; et al. (Energy and Environmental Science, 2024)
Three-dimensional/two-dimensional (3D/2D) heterojunctions in perovskite solar cells exhibit excellent optoelectronic properties and enhanced stability under mild ageing conditions. However, their performance degrades drastically under harsh ageing conditions. This study reveals the intrinsic instability of mono-ammonium based 2D perovskites (2D-mono) under photo-thermal ageing, which decompose into PbI2 and metallic lead (Pb0). The structural collapse promotes vacancy formation and facilitates iodide migration to the anode. As a result, it triggers a redox reaction that reduces the transport layer’s mobility and doping concentration, leading to a significant increase in series resistance. Compared to mono-ammonium-2D structure, di-ammonium-2D (2D-di) based interfaces demonstrate superior structural stability and effectively block iodide migration into the transporting layer. However, blocking-induced uneven iodide distribution leads to interstitial defect formation in the 3D layer, exacerbating non-radiative recombination. To address it, we propose a strategical method by incorporating 2D-di in the 3D bulk instead of on the top surface, which effectively confines mobile ions within the grain and suppresses cation phase segregation. This optimization yields stable perovskite solar cells with an extrapolated operational T80 lifetime exceeding 560 hours under harsh conditions (85°C and 2-sun illumination

Squeezing the Threshold of Metal-Halide Perovskite Micro-Crystal Lasers Grown by Solution Epitaxy - Zhou, Shuyu; Rehm, Viktor; Afify, Hany A.; Feng, Yufei; Korczak, Jędrzej; Szczerbakow, Andrzej; Story, Tomasz; Peng, Zijian; These, Albert; Barabash, Anastasia; Osvet, Andres; Brabec, Christoph; et al. (Advanced Functional Materials, 2024)
Metal halide perovskite semiconductors have demonstrated remarkable progress not only in photovoltaics and X-ray detection but also in laser technologies. Particularly appealing is the simplicity with which micro-crystallites can be epitaxially grown, thereby forming micro-resonators suitable for lasing. Here, the laser threshold is optimized by selecting excitation laser parameters and by improving material quality. The latter process is conducted for formamidinium lead tribromide, emitting in the green spectral range. Depending on the growth method and parameters, the sizes of the micro-resonators can be tuned between ≈3 and 23 micrometers. Under laser excitation systematically lower thresholds are observed for micro-resonators in the 4–7 micrometer size range, than for larger ones, irrespective of growth method. Among three optimized growth methods, epitaxial growth via antisolvent vapor-assisted crystallization exhibits the smallest threshold powers, indicating the highest material quality. This conclusion is supported by hyperspectral microscopic luminescence imaging and by transient photoluminescence. The best laser structures exhibit record threshold powers for epitaxially grown perovskites, indicating that the selected antisolvent vapor epitaxial growth holds great promises also for other perovskite materials.
CRIS-Team Scopus Importer:2024-05-10
Keywords: FAPbBr; lasing; micro-resonators; perovskites; solution epitaxy

Tailoring the Dimensionality of 2D/3D Heterojunctions for Inverted Perovskite Solar Cells - Li, Chaohui; Zhang, Kaicheng; Maiti, Santanu; Peng, Zijian; Tian, Jingjing; Park, Hyoungwon; Byun, Jiwon; Xie, Zhiqiang; Dong, Lirong; Qiu, Shudi; Bornschlegl, Andreas; Liu, Chao; et al. (ACS Energy Letters, 2024)
Interface engineering is crucial to achieving stable perovskite photovoltaic devices. A versatile approach is developed to tailor interface properties via integrating co-assembled monolayers (co-SAMs) at the p-type buried interface and by capping a two-dimensional (2D) perovskite layer at the n-type upper interface with vacuum quenching. Optimized co-SAMs promote the coverage of the hole transport layer, significantly reducing the incidence of leakage currents. Based on this foundation, we develop damp-heat-stable perovskite solar cells by precisely tailoring the fragments of 2D perovskite layers through vacuum annealing with phenethylammonium iodide. An impressive open-circuit voltage of 1.216 V is achieved, corresponding to 92% of the value determined by the detailed-balance limit, along with a power conversion efficiency of 23.68%. Ultimately, integrating co-SAMs and the vacuum-assisted annealing fabricated devices maintain 96% and 80% of initial efficiencies after 1200 and 500 h of tracking at a maximum power point under 55 and 85 °C, respectively.
CRIS-Team Scopus Importer:2024-02-23